The synthesis and spectral characterization of complexes of Co(II), Ni(II), Cu(II) and Zn(II) with a new 1,3-dioxolane derivatives of unsymmetrical vic-dioximes - Canoploat, E; Kaya, M (Polish Chemical Soc, 2005)
Two new vic-dioxime ligands containing 1,3-dioxolane ring and ethylenediamine, N'-hydroxy-2-(hydroxyimino)-N-(2-{[(2-phenyl-1,3-dioxolan-4-yl)methyl]amino}ethyl)ethan-imidamide (LIH2), N'-hydroxy-2-(hydroxyimino)-N-(2-{[(2-methyl-2-phenyl-1,3-dioxolan4-yl)methyl]amino}ethyl)ethanimidamide ((LH2)-H-2) and their complexes have been prepared from chloride salts of Co-II, Ni-II, Cu-II and Zn-II in EtOH. The authenticity of the ligands and their complexes have been established by IR, H-1- and C-13-NMR spectra, UV-visible spectroscopy, elemental analysis and magnetic susceptibility measurements. The complexes are mononuclear. Ligands form complexes [((LH)-H-1)(2)M] and [((LH)-H-2)(2)M] with a metal:ligand ratio of 1:2 with M = Co-II, Ni-II and Cu-II. Zn-II forms with ligands complexes [(Zn)((LH)-H-1)(CI)(H2O)] and [(Zn)((LH)-H-2)(Cl)(H2O)] which have a metal:ligand ratio of 1:1. The mononuclear Co-II, Ni-II and Cull complexes indicated that the metal ions are coordinated to ligands by two N atoms, as do most of the vic-dioximes. In the Zn(II) complexes the ligands are coordinated by the N and O atoms of the vic-dioximes.
Keywords: dioximes; transition metals; synthesis of vic-dioxime complexes